(3TQM hbGjI GdQhGjI aj eSGFd GdgOGjIs - (3UOQ GdTQjYI GdKGfj, YHjO Gddg Hf eSYhO Hf JGL GdTQjYI eMehO GdeMHhHj, J (B747(3g`s ((3eMdI MGLj EdjGS aj HjJ JQGHj CafOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hGdUdGI Ydi NjQ Ndbg eMeO hBdg CLeYjf jbhd GdYHO GdeJhSd Edi Gddg HCbhi GdPQjYI YHjO Gddg Hf eSYhO JGL GdTQjYIs
(3BNQgG (B:s
(3haj Zfe ePHhMI ajgG ejJI hgj Cbd JMQj hCcd aj GdGNJjGQ dCfg jMd Ccd GdejJI haj MGdI GdGVWQGQ hbGd GdTGaYj dG jHGM GdJfGhd dGf GdJMQj Odjd VQhQj hdG VQhQhIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 197s
(3eYLe GdeDdajf (B2 / 355s
(3cTa GdXfhf (B2 / 2021s
(3GdahGFO GdHgjI (B109s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs